Value chain analysis of large cardamom in eastern Himalayan road corridor of Nepal: Trade and governance - Kattel, R. R.; Regmi, P. P.; Sharma, M. D.; Thapa, Y. B. (Journal of Agriculture and Forestry University, 2020)
Large cardamom (Amomum subulatum Roxb.) is exportable high value sub-sector of Nepal producing to sell in targeted international markets. This research was done to examine value chain analysis of large cardamom from governance and trade aspects, focusing on value chain map, export scenario, and technology upgrading in eastern Himalayan road corridor (EHRC) of Nepal. Farm level information was collected from Taplejung, Jhapa and Morang districts using set of questionnaire (n=300). Focus Group Discussion, Key Informant Interview and Rapid Market Appraisal were done with enablers and traders. About 32% samples household were commercial farmers having one or more than one hectare cardamom cultivation land. About 27% households used improved dryer for curing and drying whereas majority used (72%) traditional dryer. The cost of production of one kg cardamom was estimated NRs. 656, and farmers received NRs. 344 profit margin from one kg of large cardamom sold at farm. Due to global price fluctuation, price of large cardamom has been declined drastically, although farmers are still in profit with B/C ratio of more than 1.4. The findings revealed that value chain development of large cardamom is not well structural at function, actors and enablers level whereas village/district level collectors, regional and national traders with their association and exporters were performing better marketing instead of governance of small scale producers. About 90% large cardamom was exported to India. Nepalese traders have a poor capacity and governance to export product in other counties than India due to high entry barrier to global market. There is a potential of forming global value chain development alliance, focusing to financing and upgrading strategy that would be pivotal for large cardamom intervention strategy in improving value chain function.